Faktor - Faktor Yang Mempengaruhi Partisipasi Tenaga Kerja Wanita di Indonesia - Febi Ariansyah; Satria, Doni (Media Riset Ekonomi Pembangunan (MedREP), 2024)
This research aims to determine the effect of education, wages, per capita expenditure of women and economic growth on the level of female labor force participation in Indonesia from 2018 to 2023. Quantitative research type. The object of this research was conducted in all provinces in Indonesia for the period 2018 to 2023. The Central Statistics Agency (BPS) provided the researchers with the secondary data that was used. Using the Chow, Hausman, and hypothesis tests (R2, F, and t tests), panel data regression analysis is the data analysis approach employed. The Fixed Effect Model is the panel data regression estimation model, and the E-Views 12 program is used for data processing. The study's findings show that the factors of economic growth, women's welfare, education, and income all significantly affect Indonesia's female labor force participation rate.. Partially: (1) electricity infrastructure has a positive and significant effect on the level of female labor force participation. (2) wages have no effect on the level of female labor force participation. (3) women's welfare have no effect on the level of female labor force participation. (4) Economic growth has a negative and significant effect on the level of female workforce participation.